PENGAMANAN DATA PADA APLIKASI SIJALU UNIVERSITAS SEMARANG DENGAN METODE REMOTE BACKUP & RESTORE - Adhiwibowo, Whisnumurti; Suprayogi, M Sani; Nugroho, Atmoko (Universitas Semarang, 2018)
Security of web applications should include a variety of ways, one of which is concerned about data security. Websites that already have a lot of users it is proper to consider the backup and restore strategy to prevent data loss. Besides the use of backup and restore is done on a scheduled basis should also be done at any time, so it is necessary to do the planning and use of the right tools so that the implementation is easier. Journal of Information Systems (SIJALU) University of Semarang contains data of scientific publications from researchers at tire University of Semarang and other campuses. Currently SIJALU not yet have a strategy for the prevention of data loss, this study intends to design and produce a data security benefits of using remote backup and restore. This research is expected with the data stored in SIJALU can be maintained.